ANALISIS MODERASI PROFITABILITAS PADA HUBUNGAN STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN: STUDI PADA PERUSAHAAN NON-CYCLICALS - Ineke; Viriany (Jurnal Bina Akuntansi, 2025)
ABSTRACT The purpose of this study was to examine the capital structure, and firm size effect on firm value with profitabiliy as a moderating variable in non-cyclical sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. The selected sample was 23 companies using the purposive sampling method. Data analysis using Eviews 12 and Microsoft Excel 2021. Based on the results of the t-test result, capital structure has a positive and significant effect on firm value, while firm size has a negative and insignificant effect on firm value, then profitabiliy as a moderating variable cannot strengthen the relationship between capital structure and firm size on firm value. Keywords: Capital Structure, Firm Size, Profitability, Firm Value.